2007
DOI: 10.1097/hjh.0b013e3281de72f0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myocardial hypertrophy in prehypertensive spontaneously hypertensive rats: interaction between adrenergic and nitrosative pathways

Abstract: In prehypertensive SHR, left ventricular hypertrophy is associated with adrenergic and nitrosative imbalance. Early superoxide dismutase mimetic treatment in SHR effectively reduces higher myocardial ONOO generation, sympathetic activation, and heart rate without affecting the development of myocardial hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The physiological relevance of this activation is not yet understood but, 2 aspects could be considered: a deviation of O 2 ⅐Ϫ to hydrogen peroxide, the last being involved in hypertrophy, or a compensatory mechanism to O 2 ⅐Ϫ increase that would not be sufficient to prevent cardiac hypertrophy. These questions were addressed recently in the study by Cabassi et al 15 performed on prehypertensive spontaneously hypertensive rats. These animals exhibit an overactivity of the sympathetic nervous system together with increased oxidative stress status and cardiomyocyte hypertrophy.…”
Section: -Ht 2b R Blockade Prevents O 2 ؊ -Mediated Iso-induced Carmentioning
confidence: 89%
“…The physiological relevance of this activation is not yet understood but, 2 aspects could be considered: a deviation of O 2 ⅐Ϫ to hydrogen peroxide, the last being involved in hypertrophy, or a compensatory mechanism to O 2 ⅐Ϫ increase that would not be sufficient to prevent cardiac hypertrophy. These questions were addressed recently in the study by Cabassi et al 15 performed on prehypertensive spontaneously hypertensive rats. These animals exhibit an overactivity of the sympathetic nervous system together with increased oxidative stress status and cardiomyocyte hypertrophy.…”
Section: -Ht 2b R Blockade Prevents O 2 ؊ -Mediated Iso-induced Carmentioning
confidence: 89%
“…First, the evidence for protein nitration in vivo is abundant and solid in both physiological and pathological conditions. 11,12,25 In particular, in HF, both experimental and human, nitrotyrosine protein accumulation reflects a disruption in the balance between oxygen and nitric oxide-derived oxidant formation and antioxidant defense mechanisms. 2,11 In the past decade, several experimental studies in HF, 1,6,12 but only few in humans, 14,27 suggested a potential pathogenetic link between progressive deterioration of heart function and increased protein nitration, although they rarely identified which protein was nitrated.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitated ceruloplasmin was then tested for nitrotyrosine with immunoblotting and ELISA assays (ELISA assay Kit; Oxis Research International Inc, Foster City, CA) as previously described. 25 Nitrotyrosine-bound ceruloplasmin was evaluated in serum from patients with HF and controls but also in ex vivo experiments on control serum (n=18) after incubation of peroxynitrite or decomposed peroxynitrite and in in vitro experiments (n=10) after peroxynitrite or decomposed peroxynitrite incubation of isolated purified ceruloplasmin in a phosphate buffer bath. In addition to nitrotyrosine, the evaluation of cysteine thiol oxidation after peroxynitrite or decomposed peroxynitrite incubation was performed on isolated purified ceruloplasmin in a phosphate buffer bath.…”
Section: Ceruloplasmin Immunoprecipitation and Immunoblotting For Nitmentioning
confidence: 99%
“…Moens et al (30) demonstrated that oral administration of BH 4 reversed LVH and fibrosis, recoupled endothelial NOS (eNOS), lowered oxidative stress, and ameliorated LV remodeling. However, BH 4 may have a narrow window of therapeutic dose in ameliorating LV remodeling induced by pressure overload, because a higher dose of BH 4 showed a decrease in the BH 4 -to-BH 2 ratio and fewer ameliorative effects (29). Such a paradoxical effect of BH 4 is partly due to the fact that BH 4 is sensitive to oxidation and easily converted to BH 2 under pathological conditions.…”
mentioning
confidence: 95%
“…When NOS is uncoupled, NOS-derived superoxide readily reacts with NO, generating peroxynitrite, and further decreases the bioavailability of NO. Peroxynitrite has been shown to be involved in signal transduction for cardiomyocyte hypertrophy (4,23). Therefore, improving the coupling status of NOS during pressure overload may have profound antihypertrophic and proangiogenic effects to prevent pathological LV remodeling and heart failure induced by pressure overload.…”
mentioning
confidence: 99%